Report of the Editor American Economic Journal: Macroeconomics - Davis, Steven J (American Economic Review, 2012)
The mandate of the American Economic Journal: Macroeconomics (AEJ: Macro) is to publish "studies of aggregate fluctuations and growth, and the role of policy in that context."The mandate also recognizes that research in macroeconomics interacts closely